Molecularly Targeted Therapies in Non–Small-Cell Lung Cancer Annual Update 2014. (January 2015) - Morgensztern, Daniel; Campo, Meghan J.; Dahlberg, Suzanne E.; Doebele, Robert C.; Garon, Edward; Gerber, David E.; Goldberg, Sarah B.; Hammerman, Peter S.; Heist, Rebecca S.; Hensing, Thomas; Horn, Leora; Ramalingam, Suresh S.; et al.
Abstract : There have been significant advances in the understanding of the biology and treatment of non–small-cell lung cancer (NSCLC) during the past few years. A number of molecularly targeted agents are in the clinic or in development for patients with advanced NSCLC. We are beginning to understand the mechanisms of acquired resistance after exposure to tyrosine kinase inhibitors in patients with oncogene addicted NSCLC. The advent of next-generation sequencing has enabled to study comprehensively genomic alterations in lung cancer. Finally, early results from immune checkpoint inhibitors are very encouraging. This review summarizes recent advances in the area of cancer genomics, targeted therapies, and immunotherapy.